Intralesional amphotericin B in a cat with cutaneous protothecosis - Roldán Villalobos, Wendie; Ferreira, Tássia; Gmyterco, Vanessa; Bastos, Renata; Bacher, Louise; Jagielski, Tomasz; Ribeiro, Márcio [UNESP]; Farias, Marconi (Wiley, 2023)
A domestic cat was presented with nodular lesions on the nose/muzzle and pinnae. Protothecosis was diagnosed through cytological and histopathological examination, and culture. Molecular identification confirmed Prototheca wickerhamii infection. Intralesional application of amphotericin B in conjunction with oral terbinafine resulted in a significant reduction of the nasal lesion and complete resolution of the pinnal lesion, without adverse effects.
Keywords: amphotericin B; cat; prototheca; protothecosis